2020
DOI: 10.1002/ange.202011495
|View full text |Cite
|
Sign up to set email alerts
|

Silver Single Atom in Carbon Nitride Catalyst for Highly Efficient Photocatalytic Hydrogen Evolution

Abstract: Single atom catalysts (SACs) with the maximized metal atom efficiency have sparked great attention. However, it is challenging to obtain SACs with high metal loading, high catalytic activity, and good stability. Herein, we demonstrate a new strategy to develop a highly active and stable Ag single atom in carbon nitride (Ag‐N2C2/CN) catalyst with a unique coordination. The Ag atomic dispersion and Ag‐N2C2 configuration have been identified by aberration‐correction high‐angle‐annular‐dark‐field scanning transmis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…The carrier lifetime of TiO 2 and CuSA-TiO 2 were determined to be 3.82 ns and 2.04 ns, respectively. The CuSA-TiO 2 shows a shorter PL lifetime compared to that of TiO 2 , revealing the faster electron transfer in CuSA-TiO 2 22,44 .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The carrier lifetime of TiO 2 and CuSA-TiO 2 were determined to be 3.82 ns and 2.04 ns, respectively. The CuSA-TiO 2 shows a shorter PL lifetime compared to that of TiO 2 , revealing the faster electron transfer in CuSA-TiO 2 22,44 .…”
Section: Resultsmentioning
confidence: 96%
“…However, the aggregation of SACs is inevitable during the catalytic reaction due to their high surface energy or leaching due to the unstable anchoring as the majority were synthesized by post-treatment (e.g., impregnation approach) [19][20][21] . More importantly, the larger the percentage of SACs, the higher the activity, whereas to load higher than 0.5 wt% of SACs is very challenging as the majority of the studies reported a limited amount of SACs (usually near 0.1-0.3 wt %) 1,2 onto the high surface area of substrates and it is difficult to control and reproduce 4,22,23 . Hence, obtaining the highly dispersed and high concentration of SACs remains to be the main bottleneck in photocatalytic H 2 production.…”
mentioning
confidence: 99%
“…To date, various SACs have been synthesized via anchoring single metal atoms on numerous materials [7][8][9][10][11][12][13] . Isolated metal atoms are generally stabilized by surface oxo ligands 14,15 , defects (vacancies and monoatomic step edges) [16][17][18][19] , heteroatoms [20][21][22] and con ned space [23][24][25][26] of supporting materials.…”
Section: Introductionmentioning
confidence: 99%
“…That is to say, the embedded single-atom Ag or Cu into the matrix of g-C 3 N 4 improves the photocatalytic performance of HCNS by adjusting the modulation of electronic structure rather than serving as active sites, which is different from the previously reported results that the introduced single-atom metals acting as active sites. [32][33][34][35][36][37] In addition, the apparent quantum yield (AQY) of Ag 1 N 3 -HCNS is calculated to be about 23.6% at a monochromatic light of 420 nm (Figure 3b). Moreover, the photocatalytic stability of Ag 1 N 3 -HCNS was examined for 52 h with intermittent degassing of the reaction test every 4 h (Supporting Information Figure S10).…”
Section: Figure 3 A) H 2 Evolution Rate Of Ag Np -Hcns Cu 1 N -Hcns Ag 1 N 3 -Hcns Hcns and Bulk Cn (3 Wt% Pt As Cocatalyst) B) Wavelengtmentioning
confidence: 99%